ЕЛЕКТРОМАГНІТНІ СИСТЕМИ ОБЕРТАЛЬНОГО РУХУ РІДКОГО МЕТАЛУ ДЛЯ ЕЛЕКТРОТЕХНОЛОГІЧНИХ УСТАНОВОК - Шидловський, А.К.; Гориславець, Ю.М.; Глухенький , О.І. (Інститут електродинаміки НАН України, Київ, 2012)
The results of researches of electromagnetic systems for creation rotational motion of liquid metal in electro-technological installations, obtained in the performance of research work Aspect", are given. The principle of operation of these systems is based on the use of the own magnetic field or electric current, that functionally are in such installations. Two approaches to create the motion of metal were used: at the expense of rotating magnetic field and on the basis of interaction crosstab electric and magnetic fields. The first approach is implemented in the induction channel furnaces, the second- in arc electric installations. Mathematical models for the study of physical processes in such systems are described. The results of computer simulation of electromagnetic forces and flow of molten metal in induction channel furnace and bath of vacuum-arc furnaces are given. The electromagnetic, hydrodynamic and electrodynamic parameters of these systems are determined. The specific electromagnetic torque and the average angular velocity of liquid metal were accepted as electrodynamic parameters. In addition, for the induction channel furnace with rotational movement of metal the analysis of forces acting on non-metallic inclusions (particles) that are in melt is carried out, and also for installation for refining of melt the behaviour of bubbles of refining gas in the rotational flow of liquid metal is studied. References 14. figures 11.